Green Banking and Firm Value: Examining the Effects of Firm Age, Firm Size, and Return on Assets in Indonesian Publicly Listed Banks - Defano, Pinker; Octafilia, Yusnita; Suharti, Suharti; Mahardika, Dhoni Rizky Widya (Research in Accounting Journal (RAJ), 2025)
This study aims to analyze the effect of green banking, firm age, firm size, and return on assets (ROA) on firm value in the banking sector listed on the Indonesia Stock Exchange during the 2019–2023 period. This research employs a quantitative method and utilizes secondary data obtained from financial statements accessed through idx.com and the official websites of the respective banks. The population of this study consists of 46 banking companies listed on the Indonesia Stock Exchange. The sampling technique used is a census (saturated sampling), in which all members of the population are included as the sample. The data analysis method applied in this study is path analysis using SPSS software. The analysis includes descriptive statistics, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple regression analysis, F-test, coefficient of determination (R²) test, and hypothesis testing (t-test). The results indicate that green banking has a significant negative effect on firm value, while firm age, firm size, and ROA have positive but insignificant effects on firm value in the banking sector listed on the Indonesia Stock Exchange during the 2019–2023 period.